ANALYSIS OF RESISTANCE ON FISHING VESSELS ON FISHERIES PORT, KARANGANTU SERANG - Setiawan, Naufal Arifin; Satria, Dhimas; Pinem, Mekro Permana; Suprayogi, Dedy Triawan (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Karangantu Port, located in Banten Province, plays a strategic role in supporting capture fisheries activities. However, fishing vessels operating in this port often face hydrodynamic resistance issues that affect operational efficiency. This study aims to analyze the influence of vessel speed and draft on the total resistance experienced by fishing boats. A 3D hull model was developed using SolidWorks and simulated using Maxsurf. Speed variations ranged from 5 to 12 knots, with four draft levels tested: 0.5 m, 0.7 m, 0.9 m, and 1.1 m. The results show that total resistance increases significantly with speed, particularly due to the dominance of wave-making resistance at speeds above 8 knots. Deeper drafts also lead to higher frictional resistance, caused by the increased wetted surface area. The optimal operational speed for maintaining fuel efficiency is in the range of 6 to 9 knots, with a balanced draft setting to ensure vessel stability without excessive resistance. These findings are expected to contribute to more efficient design and operation of fishing vessels at Karangantu Port.